A network based dynamic air traffic flow model for en route airspace system traffic flow optimization. (October 2017) - Chen, Dan; Hu, Minghua; Zhang, Honghai; Yin, Jianan; Han, Ke
Highlights: A dynamic air traffic flow model is developed to detect the demand-capacity imbalance. A traffic flow optimization method is proposed to minimize the operation cost when resolving the imbalance problem. Case study shows that the method can effectively optimize the en route traffic. Abstract: This study proposes a mesoscopic dynamic air traffic model based on a dynamic network for en route airspaces by characterizing the dynamics and distribution of traffic speed. Based on this model, we solve a flow optimization problem for enforcing capacity constraints with the minimum operational cost using a dual decomposition method. A case study of an en route airspace in Shanghai demonstrates the accuracy of the proposed model in successfully capturing the flow dynamics, as well as the effectiveness of the proposed optimization framework to reduce en route delays by balancing the dynamic traffic demand and airspace capacity.